Coconut Entrepreneurs’ Marketing Knowledge and Skill Development for Creative Tourism in Koh Samui - Chodchuang, Siripat; Subphonkulanan, Laphassawat; Chantanaphant, Jirayuth; Soralamb, Nuttapul (Management Institute Faculty of Economics Universitas Andalas, 2024)
Nowadays, with crucial business competitions, entrepreneurs are obliged to possess marketing knowledge and skills in order for their business to survive and grow. Thus, the purpose of this research is to study marketing readiness of coconut products’ entrepreneurs and to offer guidelines on marketing development and skill improvement for coconut entrepreneurs. The research tool is structural interviews by conducting data collection from in-depth interviews with 21 individuals whose names are in a list of information providers along with 3 focused groups being classified based on coconut products’ operators. The findings show that coconut products’ entrepreneurs possess insufficient knowledge and skills in marketing management, in another word, their readiness is dissatisfied. It is imperative that training programs be conducted to improve knowledge and skills through a curriculum on quality and product standard development; packaging design development; increasing distribution channels; product advertisement and public relation strategy development; and creative tourism. The curriculum is aimed to create outstanding points of Samui coconut product identity and the differences of Samui tourism being compared with others.